Dynamic readout of optical information based on the color-tunable emitting electron-trapping material BaAl12O19:Eu2+ toward high security level optical data storage and anticounterfeiting. Issue 8 (29th March 2023) - Wu, Junxiao; Zhao, Lei; Chen, Wenbo; Yang, Youlin; Wang, Yifan; Xu, Xuhui
Abstract : Dynamic readout of optical information based on color tunable TSL is realized. Abstract : The multiplexing level of the optical information readout process from the storage medium determines the security level in the field of optical data storage (ODS) and multiple anticounterfeiting. Realizing the emission intensity, wavelength, and color multiplexing information through the dynamic readout of optical information in a single medium can greatly improve its security level. Herein, a thermal-stimulated color-tunable emitting electron-trapping material BaAl12 O19 :Eu 2+ was developed as a deep trap-controlled ODS medium. The site occupation of Eu 2+ and trap distribution can be adjusted by different synthesis atmospheres of the samples. Compared to the static information readout process of self-reduction samples synthesized in air atmosphere, the emission intensity-wavelength-color multicomplexing of the optical information dynamic readout process was obtained on BaAl12 O19 :Eu 2+ single medium synthesized in reducing atmosphere under thermal stimulation. The dynamic changes in the emission wavelength (red-shift) and emission color (from blue to cyan) of thermally stimulated luminescence (TSL) were produced under different thermal excitation conditions (such as temperature and duration time), which was introduced by the synergistic effect between defect centers and luminescence centers with different lattice site occupation. The results provide a new strategy and feasible scheme for the dynamic readout of optical information toward information encryption technologies in ODS and multiple anticounterfeiting.